HAKEKAT PENDIDIK DALAM PENDIDIKAN ISLAM - heryati, helma (LPPM Universitas Muhammadiyah Muara Bungo, 2023)
One of the elements in education is the teacher. Educators are an important element in Islamic education, this study aims to describe the nature of educators in Islamic education. The research method used in this research is library research. Sources of research data consist of primary data sources and secondary data sources. Data analysis using content analysis. The results of the study show that, in Islamic education, there are two kinds of educators, namely parents and teachers in formal and informal schools. Educators in formal and informal schools must fulfill the characteristics of being an educator, fulfill the requirements as an educator, and fulfill their function as an educator.